2021
DOI: 10.7759/cureus.19455
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of Direct Examination, Culture, and Histopathology in the Diagnosis of Mucormycosis: Reiterating the Role of KOH Mount for Early Diagnosis

Abstract: Introduction Invasive fungal infections have always been a major cause of mortality and morbidity and are especially prevalent in the immunosuppressed groups of patients. Members of the Mucoracea family have an increasing incidence and prevalence. It has always been difficult to diagnose this condition due to various reasons. Materials and Methods This was an observational study carried out jointly by the Department of Microbiology and the Department of P… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
3
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
6

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(9 citation statements)
references
References 14 publications
(16 reference statements)
3
3
1
Order By: Relevance
“…In our study, KOH microscopy had a moderate agreement (k: 0.422) with culture; it had a high sensitivity (84.92%), specificity (61.56%), and very good NPV (87.23%) when compared with gold standard cultures. Similar findings have been reported by Mohanty et al (2021). The low PPV observed (56.90%) could be due to the low growth of Mucorales on culture [8].…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…In our study, KOH microscopy had a moderate agreement (k: 0.422) with culture; it had a high sensitivity (84.92%), specificity (61.56%), and very good NPV (87.23%) when compared with gold standard cultures. Similar findings have been reported by Mohanty et al (2021). The low PPV observed (56.90%) could be due to the low growth of Mucorales on culture [8].…”
Section: Discussionsupporting
confidence: 88%
“…However, the growth in cultures from the samples was not 100%. Walsh et al and Mohanty et al observed positivity of below 50% in cultures [8,9]. In our study, the positivity rate was only 34.2%.…”
Section: Discussioncontrasting
confidence: 66%
“…The diagnosis was confirmed by SDA Culture. Our KOH and SDA Culture findings were concordant with study done by Mohanty A et al 2021 [57] . where it was found out that out of 186 samples 6 samples (3.22%) were only positive in Culture and an another study by Begari V et.al 2019 [58] .…”
Section: Case Historysupporting
confidence: 93%
“…Mucormycosis diagnosis requires specimen culture for the genus/species identification and antifungal susceptibility testing. A direct microscopy, particularly when combined with fluorescent brighteners and dilacerating agents like KOH, can be utilised to provide quick tentative diagnosis of mucormycosis [106] . Under microscopic examination, mucorales have aseptate or semi-septate, uneven, tape-like hyphae, just as histological specimens’ even artificial septa can form as result of hyphal folding or development of one hyphae across another, just as they might in histological studies.…”
Section: Present Updated Guideline For Diagnosis Of Mucormycosismentioning
confidence: 99%